2011
DOI: 10.1071/en10142
|View full text |Cite
|
Sign up to set email alerts
|

Perfluorinated compounds in red-throated divers from the German Baltic Sea: new findings from their distribution in 10 different tissues

Abstract: Environmental context. Perfluorinated compounds are commonly used chemicals that are detected globally in all environmental matrices. We investigated the extent of contamination by perfluorinated compounds in the red-throated diver, a marine predatory bird, and observed an unusual distribution of perfluorinated compounds in tissues. The data help us to better understand the behaviour of these contaminants in organisms.Abstract. Twenty poly-and perfluorinated compounds (PFCs) were investigated in four red-throa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
17
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 40 publications
(100 reference statements)
7
17
0
1
Order By: Relevance
“…PFCAs, such as PFOA and PFNA, which were monitored in other environment investigations, showed a similar tissue distribution (liver > muscle ≥ adipose). This tissue distribution is in agreement with available literature in other investigations of fish and wildlife (Rubarth et al, 2011; Holmstrom et al, 2008; Verreault et al, 2005; Greaves and Letcher, 2013; Van de Vijver et al, 2005 and 2007). In the present study, the concentration of PFOS in albatross adipose tissues was about one of tenth of that in liver samples (3.3 ng g -1 ww vs. 36.05 ng g -1 ww).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…PFCAs, such as PFOA and PFNA, which were monitored in other environment investigations, showed a similar tissue distribution (liver > muscle ≥ adipose). This tissue distribution is in agreement with available literature in other investigations of fish and wildlife (Rubarth et al, 2011; Holmstrom et al, 2008; Verreault et al, 2005; Greaves and Letcher, 2013; Van de Vijver et al, 2005 and 2007). In the present study, the concentration of PFOS in albatross adipose tissues was about one of tenth of that in liver samples (3.3 ng g -1 ww vs. 36.05 ng g -1 ww).…”
Section: Resultssupporting
confidence: 92%
“…In the present study, the concentration of PFOS in albatross adipose tissues was about one of tenth of that in liver samples (3.3 ng g -1 ww vs. 36.05 ng g -1 ww). This distribution is consistent with the results found in red-throated divers ( Gavia stellata ) sampled from the Baltic Sea (Rubarth et al, 2011). However, the PFOS ratio of C adipose /C liver found in the present study is much higher than that found in mammal samples, such as polar bear from East Greenland (Greaves and Letcher, 2013).…”
Section: Resultssupporting
confidence: 91%
“…This trend has previously been observed in the brain of red-throated divers (Gavia stellata) from the Baltic Sea [20] as well as in the liver of polar bears and other Arctic species [2,37]. This odd-even relationship seems to be indicative of PFCA sources in the Arctic.…”
Section: Comparison With Pfcas and Pfsas In The Brains Of Other Studisupporting
confidence: 76%
“…Although concentrations of PFOS and other PFCAs and PFSAs in the liver of polar bears have been shown to be extremely high [3], no studies have investigated levels of any PFASs in other tissues or body compartments, including the brain or among brain regions [17,[19][20][21][22][23][24]. In the brain, PFOS has been detected following laboratory animal exposure [25], demonstrating its ability to cross the BBB.…”
Section: Introductionmentioning
confidence: 99%
“…PFCAs with more than 9 carbon atoms have been also detected in fish (Stahl et al, 2014) and wildlife (Ahrens et al, 2009;Rubarth et al, 2011). These findings suggest that humans are also exposed to such PFCAs.…”
Section: Introductionmentioning
confidence: 86%